2020
DOI: 10.14744/tjtes.2020.24747
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis in pregnancy: 50 case series, maternal and neonatal outcomes

Abstract: BACKGROUND:During pregnancy, the most common indication for non-obstetric surgery in acute abdomen is appendicitis. In pregnancy, appendicitis may be confused with pregnancy-related pathologies and may cause a delay in diagnosis or unnecessary surgery. The present study aims to evaluate the maternal and neonatal outcomes of patients undergoing appendectomy during pregnancy. METHODS:This study was designed retrospectively between 2011-2017. Appendicitis detection rates, admission and laboratory features, operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…Fourteen studies reported population-based data, 1012,15,22,23,26,29,31,33,35,42,45,50 three studies reported multicenter data 36,39,60 and 43 studies reported single-center data, 13,14,1621,24,25,27,28,30,32,34,37,38,40,41,43,44,4649,5159,6169 and all, expect one small prospective single-center study on 22 women,63 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies reported population-based data, 1012,15,22,23,26,29,31,33,35,42,45,50 three studies reported multicenter data 36,39,60 and 43 studies reported single-center data, 13,14,1621,24,25,27,28,30,32,34,37,38,40,41,43,44,4649,5159,6169 and all, expect one small prospective single-center study on 22 women,63 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Data on developmental delays were reported in three studies, 49,57,63 and data on congenital anomalies were reported in eight studies. 11,14,17,18,32,50,51,58 There were no cases of developmental delays. Non-obstetric surgery (n = 5453) did not affect the prevalence of congenital anomalies, the prevalence was 4.1% in both groups.…”
Section: Description Of the Studies According To The Fetal And Matern...mentioning
confidence: 97%
See 3 more Smart Citations